Testing Whether Pre-Pod-Fill Symbiotic Nitrogen Fixation in Soybean Is Subject to Drift or Selection Over 100 Years of Soybean Breeding - Thilakarathna, Malinda S.; Torkamaneh, Davoud; Bruce, Robert W.; Rajcan, Istvan; Chu, Godfrey; Grainger, Christopher M.; Szczyglowski, Krzysztof; Hill, Brett; Raizada, Manish N. (Frontiers in Agronomy, 2021)
Soybean [Glycine max (L.) Merr.] is the world’s leading legume crop and the largest oilseed crop. It forms a symbiotic relationship with rhizobia bacteria residing in root nodules that provide fixed nitrogen to host plants through symbiotic nitrogen fixation (SNF). In soybean, it has been widely reported that the highest SNF occurs at the pod-filling stage, associated with the peak demand for nitrogen. However, the majority of seed nitrogen is derived from remobilizing root/shoot nitrogen, representing cumulative SNF from the seedling stage to the pre-pod-fill stage. Therefore, the question arises as to whether there has also been selection for improved SNF at these earlier stages, or whether pre-pod-fill SNF traits have drifted. To test this hypothesis, in this study, pre-pod SNF-related traits were evaluated in soybean cultivars that span 100 years of breeding selection in the Canadian Province of Ontario. Specifically, we evaluated SNF traits in 19 pedigree-related historical cultivars and 25 modern cultivars derived from the University of Guelph soybean breeding program. Field trials were conducted at Woodstock, Ontario, Canada in 2016 and 2017, and various SNF-related traits were measured at pre-pod-fill stages (R1-R3), including nitrogen fixation capacity. Considerable variation was observed among Canadian soybean cultivars released over the past 100 years for pre-pod-fill nitrogen fixation. The modern soybean cultivars had similar or moderately higher pre-pod-fill SNF compared to the historical lines in terms of the percentage of nitrogen derived from the atmosphere (%Ndfa) and total shoot fixed nitrogen. These findings suggest that, despite direct selection by breeders, pre-pod-fill nitrogen fixation and associated SNF traits have been maintained and possibly improved in modern soybean breeding. However, the low level of pre-pod-fill SNF in some modern cultivars, and generally wide variation observed in SNF between them, suggest level of genetic drift for this trait in some pedigrees. Specific historical and modern soybean cultivars were identified as potential parents to enable targeted breeding for improved pre-pod-fill SNF. This retrospective study sheds light on our understanding of the impact of decades of recent selective breeding on pre-pod-fill nitrogen fixation traits in soybean in a temperate environment.